Toward Developing a Specific Outcome Instrument for Spine Trauma: An Empirical Cross-sectional Multicenter ICF-Based Study by AOSpine Knowledge Forum Trauma. Issue 17 (1st September 2015) - Oner, F. Cumhur; Sadiqi, Said; Lehr, A. Mechteld; Aarabi, Bizhan; Dunn, Robert N.; Dvorak, Marcel F.; Fehlings, Michael G.; Kandziora, Frank; Post, Marcel W.; Rajasekaran, S.; Vialle, Luiz; Vaccaro, Alexander R.
Abstract : Study Design: Empirical cross-sectional multicenter study. Objective: To identify the most commonly experienced problems by patients with traumatic spinal column injuries, excluding patients with complete paralysis. Summary of Background Data: There is no disease or condition-specific outcome instrument available that is designed or validated for patients with spine trauma, contributing to the present lack of consensus and ongoing controversies in the optimal treatment and evaluation of many types of spine injuries. Therefore, AOSpine Knowledge Forum Trauma started a project to develop such an instrument using the International Classification of Functioning, Disability and Health (ICF) as its basis. Methods: Patients with traumatic spinal column injuries, within 13 months after discharge from hospital were recruited from 9 trauma centers in 7 countries, representing 4 AOSpine International world regions. Health professionals collected the data using the general ICF Checklist. The responses were analyzed using frequency analysis. Possible differences between the world regions and also between the subgroups of potential modifiers were analyzed using descriptive statistics and Fisher exact test. Results: In total, 187 patients were enrolled. A total of 38 (29.7%) ICF categories were identified as relevant for at least 20% of the patients. Categories experienced as a difficulty/impairment were most frequently related to activities and participation (n = 15), followed by body functions (n = 6), and body structures (n = 5). Furthermore, 12 environmental factors were considered to be a facilitator in at least 20% of the patients. Conclusion: Of 128 ICF categories of the general ICF Checklist, 38 ICF categories were identified as relevant. Loss of functioning and limitations in daily living seem to be more relevant for patients with traumatic spinal column injuries rather than pain during this time frame. This study creates an evidence base to define a core set of ICF categories for outcome measurement in adult spine trauma patients. Level of Evidence: 4 Abstract : To have a better understanding of the actual problems patients with traumatic spinal column injuries are facing, an empirical cross-sectional multicenter study was conducted. Thirty-eight International Classification of Functioning, Disability and Health categories were identified as most relevant. Loss of functioning and limitations in daily living were found to be more relevant than pain.